Puerto Rican Labor History 1898-1934 : Revolutionary Ideals and Reformist Politics - Sanabria, Carlos (Lexington Books, 2017)
This book presents a history of the organized labor movement in Puerto Rico from US colonial domination in 1898 to the Great Depression in the 1930s. Despite the early influence of revolutionary ideologies, the organized workers' movement sought to create change through the organization of labor and participation in electoral politics.